EL-"UKÛBÂTÜ'T-TA'ZÎRIYYETÜ VE SULTATÜ'L-KÂDÎ FÎ TAKDÎRIHA FI'L-FIKHI'L-İSLAMÎ - BRA, DLER HAMA KAKA (Fırat Üniveristesi, 2020)
Bu araştırma, İslam Hukukunda Ta'zir cezalarını ve hakimin bu cezaları takdir yetkisini ve sınırlarını tespit etmeyi amaçlamaktadır. Çalışmamız dört bölümden oluşmaktadır: Birinci bölüm'de "Ta'zir" kavramının anlamı, meşruiyeti, ta'zir cezalarının amaçları, türleri hakkında bilgi verilmiştir. İkinci bölüm'de İslam Hukukunda Hâkimin cezaları takdir etme yetkisi ve bu yetkinin sınırları tespit edilmiştir. Üçüncü bölüm'de, Ta'zir cezasının tespitine dair genel ilkeler ortaya konmuştur. Bu bölümde, cinayeti işleyen kişi, cinayete maruz kalan kişi ve cinayetin özelliğine göre farklılık gösterebileceği üzerinde durulmuştur. Dördüncü bölüm'de ise Ta'zir cezalarının şer'i nasların amaçları açısından kayıt ve şartları ele alınmıştır. Hakimin bu cezaları tespitte şeri nassların ve icma'i hükümlerin amaçlarının dışına çıkamayacağı üzerinde durulmuştur. Anahtar Kelimeler: Ukubat, Ta'azir, Hakimin yetkisi, Davabıt, Sukût.

This research investigated about to explain the discretion punishments and the authority of the judge in their estimation in Islamic jurisprudence, and this research divided into four sections. First section: investigate the meaning of Discretion (Ta'zir), its legitimacy, its purposes, types, and reasons for its drop. Second section: ınvestıgate the judge's authority to estimate its penalties, the criteria for assessing the sentence, and the meaning of the judge's authority. Third section: talks about the controls for assessing the discretionary punishment, considering the perpetrator, the victim and the felony, the officer of the motive for committing the crime, controlling the crime frame and the position of Islamic jurisprudence in the punishment frame, and the relation between the Sharia ruling and modern frames. The fourth section, investigated about restricting the discretion punishment, considering the provisions of the Sharia and its general purposes, restricting the judge to arbitrate by Qur'an, Sunnah and consensus, and restricting it to the purposes of general Sharia. Keywords: punishments, Discretion ,The authority of judge, Discretion controls, the fall.
The discretion punishments and the judge's authority to estimate them in Islamic jurisprudence
Keywords: Din